2013
DOI: 10.7448/ias.16.1.18466
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV status to children in resource‐limited settings: a systematic review

Abstract: IntroductionInforming children of their own HIV status is an important aspect of long-term disease management, yet there is little evidence of how and when this type of disclosure takes place in resource-limited settings and its impact.MethodsMEDLINE, EMBASE and Cochrane Databases were searched for the terms hiv AND disclos* AND (child* OR adolesc*). We reviewed 934 article citations and the references of relevant articles to find articles describing disclosure to children and adolescents in resource-limited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
264
5
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(311 citation statements)
references
References 47 publications
32
264
5
7
Order By: Relevance
“…Such silences persist even after young people have been "disclosed" to, although many young people grow up unaware of their HIV status (Vreeman et al 2013). Silence often covers the circumstances of their infection and their biological parents.…”
Section: Adherence In Hiv: Adults and Young Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Such silences persist even after young people have been "disclosed" to, although many young people grow up unaware of their HIV status (Vreeman et al 2013). Silence often covers the circumstances of their infection and their biological parents.…”
Section: Adherence In Hiv: Adults and Young Peoplementioning
confidence: 99%
“…Yet, young people who have access to care face a host of complex challenges . Existing literature covers the scale of adherence problems in this population (Kim et al 2014;Hudelson and Cluver 2015), interventions to address these (Mavedzenge et al 2014), and caregivers' views about managing young people's knowledge about their HIV status and their adherence to medication (Vreeman et al 2013). Much less is known about young people's own perspectives about growing up with HIV and on ART.…”
mentioning
confidence: 99%
“…These targets were dubbed "90-90-90": to have 90% of all people living with HIV knowing their status, 90% of all people diagnosed with HIV receiving sustained antiretroviral therapy, and 90% of all people receiving antiretroviral therapy achieving viral suppression (48). Up to 81% of African adolescents already living with HIV do not know their HIV status (38,39,(49)(50)(51). One study from Zimbabwe reported that 80% of ALHIV in their study cohort were infected from MTCT and 15% from sexual transmission (51).…”
Section: The Case For Expanding Adolescent Access To Hiv Testing and mentioning
confidence: 99%
“…Disclosure is achieved using tools and languages appropriate for the child's developmental capacity such as storytelling, cartoons, drama and use of fl ip charts 13 . Vreemanet al 12 reported level of status disclosure to be between 0 to 69.2%. Mialky et al 14 reported 43% disclosure rate with mean age of nine years, 23% of them have disclosed status to school authority, while Brown et al 15 in a study in Nigeria reported a lower level of status disclosure (13.0%).…”
Section: Introductionmentioning
confidence: 99%
“…Mialky et al 14 reported 43% disclosure rate with mean age of nine years, 23% of them have disclosed status to school authority, while Brown et al 15 in a study in Nigeria reported a lower level of status disclosure (13.0%). Common barriers to status disclosure in the review by Vreeman et al 12 were fear that the child would disclose HIV status to others, fear of stigma and concerns of emotional and physical health of child.…”
Section: Introductionmentioning
confidence: 99%